Real-Time Functional Magnetic Resonance Imaging Dyadic Neurofeedback for Emotion Regulation: A Proof-of-Concept Study - Kerr, Kara L.; Ratliff, Erin L.; Cohen, Zsofia P.; Fuller, Stormie; Cosgrove, Kelly T.; DeVille, Danielle C.; Misaki, Masaya; Morris, Amanda Sheffield; Bodurka, Jerzy (Frontiers in Human Neuroscience, 2022)
Real-time fMRI (rt-fMRI) neurofeedback can be used to non-invasively modulate brain activity and has shown initial effectiveness in symptom reduction for psychiatric disorders. Neurofeedback paradigms often target the neurocircuitry underlying emotion regulation, as difficulties with emotion regulation are common across many psychiatric conditions. Adolescence is a key period for the development of emotion regulation, with the parent-adolescent relationship providing an important context for learning how to modulate one’s emotions. Here, we present evidence for a novel extension of rt-fMRI neurofeedback wherein a second person (the parent) views neurofeedback from the focal participant (adolescent) and attempts to regulate the other person’s brain activity. In this proof-of-concept study, mother-adolescent dyads (n = 6; all female) participated in a dyadic neurofeedback protocol, during which they communicated via active noise-canceling microphones and headphones. During the scan, adolescents described current emotionally upsetting situations in their lives, and their mothers responded while viewing neurofeedback from the adolescent’s right anterior insular cortex (aIC)—a key hub for emotion-related processing. The mother was instructed to supportively respond to her daughter’s negative emotions and attempt to downregulate the aIC activity. Mean right aIC activation during each run was calculated for each adolescent participant, and results revealed a downward trend across the session (β = −0.17, SEβ = 0.19, Cohen’s f2 = 0.03). Results of this proof-of-concept study support further research using dyadic neurofeedback to target emotion-related processing. Future applications may include therapist-client dyads and continued research with parents and children. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT03929263].